2007
DOI: 10.1111/j.1527-5299.2007.07122.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered Left Ventricular Diastolic Performance in Oncologic Patients Treated With Epirubicin

Abstract: Anthracyclines confer an increased risk of cardiotoxicity. The authors evaluated left ventricular (LV) performance in patients treated with epirubicin. Sixty-eight patients with malignancies (study group), treated with epirubicin < or = 450 mg/m2, and a matched control group of 68 cancer patients who had not started chemotherapy were evaluated by Doppler echocardiography. The authors assessed LV diastolic function by measuring the transmitral flow: the maximal velocity of the E and A waves, the Emax/Amax ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Diastolic dysfunction and increase in LV filling pressure occur in earlier stages of various forms of HF. Comprehensive evaluation of diastolic function, using conventional parameters is also recommended, and some previous studies reported early changes of diastolic functional parameters [17,18]. However, in a more recent study, e' value showed only insignificant changes between patients with CTRCD and ones without it [19], and similar tendency was observed in our results.…”
Section: Discussionsupporting
confidence: 88%
“…Diastolic dysfunction and increase in LV filling pressure occur in earlier stages of various forms of HF. Comprehensive evaluation of diastolic function, using conventional parameters is also recommended, and some previous studies reported early changes of diastolic functional parameters [17,18]. However, in a more recent study, e' value showed only insignificant changes between patients with CTRCD and ones without it [19], and similar tendency was observed in our results.…”
Section: Discussionsupporting
confidence: 88%
“…However, these changes in diastolic parameters were still mostly within the normal range and were poorly correlated between resting diastolic abnormalities post-anthracycline treatment and reduction in LV systolic function [59]. Two other recent studies, (one of 68 patients with different malignancies treated with epirubicin [60] and the other comprising 20 breast cancer patients who were treated with anthracyclines [61]) demonstrated early changes in LV diastolic function. The value of diastolic abnormalities in predicting the development of left ventricular systolic dysfunction at 3 months was suggested in three small studies [55, 59, 61].…”
Section: Diastolic Parameters and Chemotherapy Cardiotoxicitymentioning
confidence: 99%
“…A subsequent study of 20 asymptomatic breast cancer patients with normal systolic function who were treated with anthracyclines also reported that more than 50 % of patients treated with anthracyclines had impaired early peak flow velocity to atrial peak flow velocity (E/A) ratio, deceleration time (DT), and isovolumetric relaxation time (IVRT) which persisted throughout the follow-up period of 29 months after discontinuation of anthracyclines [43]. Two more recent studies, (one of 68 patients with different malignancies treated with epirubicin [44] and the other comprising 20 breast cancer patients who were treated with anthracyclines [45]) demonstrated early changes in LV diastolic function. Neither of these studies, nor any of the earlier studies demonstrated prognostic value or correlation between changes in the diastolic parameters and the development of late cardiotoxicity.…”
Section: Evaluating Cardiac Dysfunctionmentioning
confidence: 99%